On the joint preprocessing techniques for OFDM-based cooperative network MIMO systems - Sheu, Jeng-Shin; Hui-Hsieh, Chia; Huang, Kuan-Ming (Journal of the Chinese Institute of Engineers, 2015)
Next-generation (4G) systems are designed to support universal frequency reuse (UFR) and adopt orthogonal frequency-division multiplexing (OFDM) to achieve best use of their valuable spectra. Unfortunately, the implementation of UFR leads to unacceptable interference levels near cell borders. To control this, 4G systems adopt network multiple-input multiple-output (MIMO), an elaborate coordination among adjacent cells, to improve coverage and cell-edge throughput. Unfortunately, for multi-cell coordination, most studies on this subject have examined the corresponding information-theoretic capacities and only a few joint preprocessing schemes have been investigated for narrowband non-OFDM-based systems in flat fading channels. Instead of information-theoretic capacity, this paper derives various joint preprocessing techniques for OFDM-based network MIMO in wideband multipath fading channels. They include joint time-division multiple access (J-TDMA), joint zero-forcing (J-ZF), joint minimum mean square error (J-MMSE), and joint null-space decomposition (J-NSD). The J-TDMA scheme is free from co-channel interference (CCI) at the cost of spectral efficiency. The J-ZF scheme enables complete suppression of interference, but demands higher transmitter power for the precoding process. The J-MMSE yields a performance close to the CCI-free J-TDMA scheme, by making an acceptable compromise between interference suppression and transmitter power efficiency. In J-NSD, the CCI is completely removed, but signal transmission is confined to a reduced subspace.